Answer :
I believe it’s asking you to combine the functions so when you combine like terms you have 2x+3x= 5x and you have -2+1= -1 so the answer is c. 5x-1
Answer:
C. 5x-1
Step-by-step explanation:
We are asked to find:
(f+g)(x)
This basically is asking us to add f(x) and g(x)
(f+g)(x)=f(x)+g(x)
We know that f(x)=3x-2 and g(x)=2x+1
f(x)+g(x)
(3x-2)+(2x+1)
Combine like terms. Add all the terms with variables, then add all the terms without variables.
(3x+2x) + (-2+1)
5x+(-2+1)
5x+-1
5x-1
(f+g)(x)=5x-1
Therefore, C. 5x-1 is the correct answer choice.